LESI ORAL TERKAIT LEUKEMIA MIELOID KRONIK: LAPORAN KASUS - Mega Rafika; Rian Setiadhi (ODONTO : Dental Journal, 2019)
Background: Oral lesion is one the clinical signs found in chronic myeloid leukemia (CML). CML is a myeloid cell neoplasm that have oral manifestations such as gingival hyperplasia, spontaneous haemorrhage, petechiae, oral infection, mucosal pallor, and ulceration. The purpose is to find out how to diagnose and oral lesions associated CML to occure, so the dentist could provide the right therapyCase Management: 46 years old male was referred from Internal Medicine Department with diagnosis CML. The patient complained of pain at the right upper gum. Cheilitis exfoliative was found at the extra oral examination, while intra oral examination found ulcer at the palate. Blood test result showed decreases of Haemoglobin, Hematocrite, erythrocytes which showed iron deficiency anemia causes disruption of oral mucosal integrity, thereby facilitating oral ulcerations. Based on history, clinical examination and laboratory investigation, intra-oral abnormality was diagnosed as oral lesion associated CML. Triamcinolone acetonide 0.1% in orabase as theraphy oral lesion, vaseline album for management exfoliative cheilitis, and Surbex Z® as multivitamin. Oral ulcer improved within 6 weeks.Conclusion: The diagnosis oral lesions associated CML can be diagnosed based on history, clinical examination and laboratory investigation. Oral ulcers in this patient caused by iron deficiency anemia.